2017
DOI: 10.5005/jp-journals-10024-2031
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Dental Caries and Body Mass Index-for-age among Schoolchildren of Jazan City, Kingdom of Saudi Arabia

Abstract: Objective: To analyze and report the type of relation present between dental caries and body mass index (BMI)-for-age among schoolchildren in Jazan region of Kingdom of Saudi Arabia. Materials and methods:A cross-sectional study with multistaged random sampling technique was designed to recruit the sample of schoolchildren. Caries was examined using the World Health Organization recommended "decayed and filled teeth"/"decayed missing and filled teeth (dft/DMFT)" method. The BMI-for-age was calculated using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 26 publications
3
17
1
4
Order By: Relevance
“…Another explanation for the inverse association might be that children with untreated caries could experience pain and infection, thus preventing them from consuming adequate nutrition. In addition, other factors that contribute to overall wellbeing could be affected, including the ability to sleep, which in turn may lead to malnutrition and growth impairment [12, 18, 20, 25, 36]. The wider literature suggests that underweight children gained weight after receiving dental treatment [19, 50].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another explanation for the inverse association might be that children with untreated caries could experience pain and infection, thus preventing them from consuming adequate nutrition. In addition, other factors that contribute to overall wellbeing could be affected, including the ability to sleep, which in turn may lead to malnutrition and growth impairment [12, 18, 20, 25, 36]. The wider literature suggests that underweight children gained weight after receiving dental treatment [19, 50].…”
Section: Discussionmentioning
confidence: 99%
“…While some studies reported more dental caries in boys [19, 20], Quadri et al [12] found more dental caries in girls. By contrast, some studies concluded that there is no difference in dental caries between both genders [18, 25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Entretanto, outros autores não demonstraram essa relação (Silva et al, 2016;Khadri et al, 2018;Carson, 2018;Paisi et al, 2018). Alguns estudos recentes não encontraram uma associação entre cárie dental e obesidade, quando avaliaram a cárie precoce da infância (Aluckal et al, 2016;Krishna et al, 2017) e cárie dental em crianças e adolescentes (Almerich-Torres et al, 2016;Farsi et al, 2016;Guizar et al, 2016;Liang et al, 2016;Farsi e Elkhodary, 2017;Krishna et al, 2017;Kumar et al, 2017;Quadri et al, 2017), evidenciando que essa associação pode ser variável, de acordo com a população avaliada.…”
Section: Avaliação Dos Defeitos Do Desenvolvimento Do Esmalte (Ddes)unclassified